Techno-Economic and Feasibility Assessment of Cryogenic Distillation Membrane (CDM) for Purification Natural Gas from CO2 - Bachtiar, Agra Y.; Annas, Ayyub C.; Fajrin, Alifah N. A.; Rizwan, Muhammad H.; Kartikasari, Indah R. (Indonesian Journal of Energy, 2021)
It is estimated that the energy demand in the world at 2050 will increase by 52% relative to 2017. In Indonesia, it was predicted the deficit energy at natural gas sector occurred as much as 17.5 BSCF in 2020 and the deficit will increase to 3,327 BSCF in 2050. Nevertheless, the natural gas that Indonesia produced has impurities of 70% CO2 and 0.6% H2S, while the hydrocarbon only 28.1%, that makes the heating value of natural gas become lower compared to common natural gas. Therefore, the process of separating the impurities of CO2 and H2S from hydrocarbon is needed to increase the heating value and to get pure natural gas. One of alternatives that can solve the problem is Cryogenic Distillation Membrane (CDM). The CDM process integrates the process of cryogenic distillation and cryogenic membrane to separate impurities from hydrocarbon. It has been proven that cryogenic distillation can decrease CO2 concentration from 70% to 3%, and rise up hydrocarbon purity from 70% to 95%. Moreover, cryogenic membrane can increase the purity of natural gas from 95% to 98%. Therefore, CDM process is expected as appropriate process to get rid the impurities and give high purity of natural gas. Based on the calculation through simulation using software ASPEN HYSYS, the CDM process is beneficial because it gives capture rate CO2 up to 99%, decreases the purity CO2 from 70% to 0.001%, reduces the purity H2S from 0.6% to 0.02%, increases natural gas purity from 28.1% to 98%, raises the heating value from 284.5 Btu/SCF to 988.4 Btu/SCF and can generate valuable byproduct CO2 liquid.